2017
DOI: 10.1126/science.aam6393
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to malaria through structural variation of red blood cell invasion receptors

Abstract: The malaria parasite Plasmodium falciparum invades human red blood cells via interactions between host and parasite surface proteins. By analyzing genome sequence data from human populations, including 1269 individuals from sub-Saharan Africa, we identify a diverse array of large copy number variants affecting the host invasion receptor genes GYPA and GYPB. We find that a nearby association with severe malaria is explained by a complex structural rearrangement involving the loss of GYPB and gain of two GYPB-A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
221
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(259 citation statements)
references
References 77 publications
20
221
2
1
Order By: Relevance
“…Glycophorins are sialoglycoproteins abundantly expressed on the erythrocyte membrane, where they play a functional role in invasion by Plasmodium falciparum. In a recent follow-up study, the authors identified an array of large copy number variants (CNVs) affecting the GYPA and GYPB genes (Leffler et al, 2017). One of the identified CNVs (DUP4) is associated with resistance to severe malaria and explains the GWAS association signal (Malaria Genomic Epidemiology Network et al, 2015).…”
Section: Gwass For Parasitic and Prion Diseasesmentioning
confidence: 99%
“…Glycophorins are sialoglycoproteins abundantly expressed on the erythrocyte membrane, where they play a functional role in invasion by Plasmodium falciparum. In a recent follow-up study, the authors identified an array of large copy number variants (CNVs) affecting the GYPA and GYPB genes (Leffler et al, 2017). One of the identified CNVs (DUP4) is associated with resistance to severe malaria and explains the GWAS association signal (Malaria Genomic Epidemiology Network et al, 2015).…”
Section: Gwass For Parasitic and Prion Diseasesmentioning
confidence: 99%
“…All of these differences are compounded by the fact that many of the studies use different definitions of clinical malaria, which makes it difficult to draw conclusions and compare studies. To address this problem, a recent sub-study from a large multi-centre casecontrol study of severe malaria (Malaria Genomic Epidemiology Network, 2014) reported an analysis of multiple allelic forms of G6PD deficiency in 11 countries from Africa and Asia using a set of 135 single nucleotide polymorphisms (Clarke et al, 2017). This study reported that increasing levels of G6PD deficiency are associated with decreasing risk of cerebral malaria, but with increased risk of severe malarial anaemia.…”
Section: Enzymatic Deficienciesmentioning
confidence: 99%
“…More so, disease states are a result of a two-way interaction that occurs between the host cells or tissues and the microorganisms. As per the chain of infection model, host-pathogen interactions can lead to either host immunity or an aggravated immune response due to infection, depending on six factors including the susceptibility of the host, route of entry and colonization potential of the microbe (Figure 1) [5,6]. Recent years have seen a surge in interest in understanding this complex interplay between the microbes and the host organism.…”
Section: Introductionmentioning
confidence: 99%